2016
DOI: 10.1016/j.ajog.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma angiogenic index-1 (placental growth factor/soluble vascular endothelial growth factor receptor-1) is a biomarker for the burden of placental lesions consistent with uteroplacental underperfusion: a longitudinal case-cohort study

Abstract: Background Placental lesions consistent with maternal vascular underperfusion (MVU) are thought to be pathogenically linked to preeclampsia, small-for-gestational-age newborns, fetal death, and spontaneous preterm labor and delivery; yet, these lesions cannot be diagnosed antenatally. We previously reported that patients with such conditions and lesions have an abnormal profile of the angiogenic placental growth factor (PlGF) and anti-angiogenic factors [e.g., soluble vascular endothelial growth factor recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 173 publications
2
53
0
1
Order By: Relevance
“…Elevated concentrations of presumed anti-inflammatory protectors of the brain and retina, [5558] such as erythropoietin and thyroid stimulating hormone, accompany systemic inflammation,[15, 59, 60] which contributes to brain damage. [5961] Consequently, our second null hypothesis postulates that postnatal systemic inflammation is not associated with top quartile concentrations of NT-4, BDNF, or bFGF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated concentrations of presumed anti-inflammatory protectors of the brain and retina, [5558] such as erythropoietin and thyroid stimulating hormone, accompany systemic inflammation,[15, 59, 60] which contributes to brain damage. [5961] Consequently, our second null hypothesis postulates that postnatal systemic inflammation is not associated with top quartile concentrations of NT-4, BDNF, or bFGF.…”
Section: Methodsmentioning
confidence: 99%
“…[5961] Consequently, our second null hypothesis postulates that postnatal systemic inflammation is not associated with top quartile concentrations of NT-4, BDNF, or bFGF. Our logistic regression models adjusted for 3 variables, indicated delivery only, birth weight Z-score < −2 only, and both indicated delivery and birth weight Z-score < −2 (Tables 2–4).…”
Section: Methodsmentioning
confidence: 99%
“…We previously proposed that pathology of the placental bed, primarily through ischemia and/or other mechanisms such as a maternal-fetal immune response, may lead to preeclampsia, small for gestational age, preterm labor with intact or ruptured membranes, abruptio placentae, and fetal death; and why a similar insult would result in different clinical phenotypes depends on genetic and environmental factors and time of onset, duration, and extent of the ischemic insult [160]. Korzeniewski et al [161] recently demonstrated that maternal plasma angiogenic index-1 concentration ratios seem to reflect the burden of uteroplacental vasculopathy indicated by histologic examination of the placenta, regardless of clinical diagnosis. The time order between changes in plasma angiogenic index-1 concentration ratios and placental features consistent with maternal vasculopathy, however, remains to be determined.…”
Section: Commentmentioning
confidence: 99%
“…However, hints have begun to emerge. The balance of angiogenic and anti-angiogenic factors appears to be key in the establishment of a successful and functional utero-placental circulation (8186). A deficiency in angiogenic factors was first implicated in the pathogenesis of preeclampsia (8795) and subsequently discovered to play a role in SGA/fetal growth restriction (93, 96), fetal death(97, 98), spontaneous preterm labor (99), Ballantyne syndrome (100), twin-to-twin transfusion syndrome (101), etc.…”
Section: Are There Biomarkers That Identify Patients With Suspected Pmentioning
confidence: 99%